2007
DOI: 10.1007/bf03403711
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from a Canadian Public Health Prenatal Screening Program for Hepatitis B

Abstract: Background: Without appropriate prophylaxis, the rate of vertical transmission of hepatitis B virus (HBV) can be as high as 95%. Alberta's provincial prenatal program screens all pregnant women for HBV, and provides prophylaxis to infants born to HBV-infected women. Canadian data on the outcomes of such programs are limited. Methods: We conducted a retrospective review of data from pregnant Albertan women who were Hepatitis B Surface Antigen (HBsAg) positive from 1997-2004. We describe the frequency of hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
(17 reference statements)
2
7
1
Order By: Relevance
“…This rate is lower than those reported in two other studies (7.4% in Korea in 2008 [21] and 2.1% in Canada in 2007 [22]) and similar to that of another study (1.54% in China in 2013 [16]).…”
Section: Discussionsupporting
confidence: 76%
“…This rate is lower than those reported in two other studies (7.4% in Korea in 2008 [21] and 2.1% in Canada in 2007 [22]) and similar to that of another study (1.54% in China in 2013 [16]).…”
Section: Discussionsupporting
confidence: 76%
“…The fact that these children did not receive HBIG may have contributed to the breakthrough, even though the additional effect of HBIG to active vaccination has not been fully established [54] . It is widely accepted and recommended that the most efficient precaution for prevention of perinatal HBV transmission is screening pregnant women for HBsAg and the immediate administration of one infant dose of hepatitis B immune globulin (HBIG) along with the first hepatitis B vaccine dose within 12 hours after birth, followed by the second and the third vaccine dose at 1 and 6 month of age [55] , [56] , [57] , [58] , [59] .…”
Section: Discussionmentioning
confidence: 99%
“…Between 2000 and 2005, there were 1253 pregnant women identified as being HBsAg positive. Although we were not able to determine the number of infants who received immunoprophylaxis or underwent follow‐up for the entire study period, our previous data reported that 82% of infants between 2002 and 2004 received complete immunoprophylaxis and follow‐up serology [17].…”
Section: Methodsmentioning
confidence: 99%
“…It is unclear whether these same patterns are seen among the mothers of infants failing HBV prophylaxis in Alberta. In a recent evaluation of the Alberta Hepatitis B prenatal screening programme it was noted that 2.1% of infants born to HBsAg-positive mothers with complete vaccination and follow-up failed vaccination and became infected with HBV [17]. To better understand the reasons for this vaccine failure, we conducted a case-control study to determine factors associated with HBV vaccine failure and perinatal transmission of infection.…”
Section: Introductionmentioning
confidence: 99%